Предмет: Алгебра,
автор: Аноним
решите пожалуйста) упростите выражение (b-1)^2-(b+4)(b-2) и найдите его значение при b=-0,7
Ответы
Автор ответа:
0
(b - 1)^2 - (b + 4)(b - 2) =
= b^2 - 2b + 1 - (b^2 - 2b + 4b - 8) =
= b^2 - 2b + 1 - (b^2 + 2b - 8) =
= b^2 - 2b + 1 - b^2 - 2b + 8 =
= - 4b + 9
При b = - 0,7
(-4)*(-0,7) + 9 = 4*0,7 + 9 = 11,8
= b^2 - 2b + 1 - (b^2 - 2b + 4b - 8) =
= b^2 - 2b + 1 - (b^2 + 2b - 8) =
= b^2 - 2b + 1 - b^2 - 2b + 8 =
= - 4b + 9
При b = - 0,7
(-4)*(-0,7) + 9 = 4*0,7 + 9 = 11,8
Похожие вопросы
Предмет: Обществознание,
автор: altynovasaikal18
Предмет: Алгебра,
автор: Artur0760
Предмет: История,
автор: konysbibinur
Предмет: Химия,
автор: стекляшкин
Предмет: Физика,
автор: Аноним